Avaliação de doses de nitrogênio no desempenho agronômico em experimentos com cultivares comerciais de milho variedade e híbrido em duas condições ambientais - Franciscatte, Walmir (2023)
Corn is one of the most important cereals produced in the country and its productivity, both of the variety cultivar and the hybrid, are directly proportional to fertilization and water availability. Based on the importance of nitrogen in corn yield, the present work aimed to evaluate nitrogen rates of two commercial cultivars, one variety and the other hybrid, in two production environments, a center pivot irrigation environment with higher soil fertility and the other rainfed environment with lower fertility, close to around 400 meters, located at UFSCar campus Lagoa do Sino, Buri, SP. For this, four experiments were installed, each with a randomized block design, with five nitrogen doses (30, 60, 90, 120 and 150 kg of N ha-1), five replications and one cultivar, in such a way that one variety and one hybrid were tested in each environment, arranged in parallel, in a Red Latosol with clayey texture and flat to gently undulating relief. Due to the distribution of rainfall, it was not necessary to irrigate, and fertility was the differential between the environments. The following parameters were evaluated: ear mass with straw per plant, grain weight per plant, length and diameter of the ear (without straw). Sowing was carried out on November 21, 2022, in a no-tillage system, using 20:10:10 fertilizer at a dose of 300 kg ha-1, incorporated in a continuous fillet. The N rates were applied as topdressing, with the Urea fertilizer manually distributed in two rows, alternately, 23 days after sowing. Through the variations of the results analyzed, according to the low fit to the linear model in most of the attributes studied and, probably, due to the planting fertilization and distribution and intensity of rainfall, it was concluded that the different doses of nitrogen fertilization in topdressing provided little increase in productivity and its components.